Morphosyntax and Phonology of Agreement in Turkish. (25th March 2021) - Güneş, Güliz
Abstract: This article offers a new morphosyntactic account of subject agreement in the Turkish verbal domain. The account is based on a combination of well‐known, novel, and overlooked observations about the distribution and prosody of verbal agreement. In Turkish, when certain morphosyntactic requirements are met and the verb is focused, as in fragment answers with ellipsis, the agreement morpheme can be parsed inside or outside of the prosodically prominent part of the verbal domain that constitutes the fragment answer. I claim that this optionality is a reflex of how the morphemes that constitute the verbal domain are postsyntactically concatenated. In particular, I argue that an agreement morpheme either lowers together with its host ( full lowering ) or is stranded when its host lowers ( partial lowering ). In full lowering, agreement is contained within the prominent part of the verbal domain, whereas in partial lowering, agreement falls outside of this prominence domain. I also show that the prosodic variability in question is observed only when two related noncanonical realizations of agreement are possible: medial agreement and double agreement. The Vocabulary Insertion rules that I postulate for the subject‐agreement paradigms of the Turkish verbal domain capture the acceptable cases of medial and double agreement and successfully predict in which environments medial agreement is optional and in which environments it is obligatory.